2017
DOI: 10.1002/chem.201701700
|View full text |Cite
|
Sign up to set email alerts
|

Selective Adsorption and Separation of Organic Dyes with Spherical Polyelectrolyte Brushes and Compressed Carbon Dioxide

Abstract: Dye-containing wastewater has caused serious environmental pollution. Herein, rationally designed spherical polyelectrolyte brushes (SPBs) with cationic charges, polystyrene-poly(2-aminoethylmethacrylate hydrochloride) (PS-PAEMH) as the absorbent, and compressed carbon dioxide as the antisolvent are proposed for the separation of the anionic dye eosin Y (EY) from a solution of mixed dyes. The adsorption behavior of EY onto PS-PAEMH was highly dependent on CO pressure, contact time, and initial concentration. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…In order to verify the improvement of photocatalytic performance of ZnTiÀ PW-500 and the mechanism of photoreduction process, DRS, EIS, i-t and PL tests were performed. [62][63][64] Compared with the DRS (Figure 5a) of ZnTiÀ PW 12 and ZnTi-LDH, it can be found that the absorption edge of ZnTiÀ PW 12 increases. After calcining ZnTiÀ PW 12 at 500 °C, the adsorption edge shifts to higher wavelength region even to the visiblelight region, indicating that calcination at 500 °C improves the absorption of visible light irradiation, which may be ascribed to PW 12 and the heterojunctions structure of ZnO and TiO 2 .…”
Section: Photoelectrochemical Propertiesmentioning
confidence: 95%
“…In order to verify the improvement of photocatalytic performance of ZnTiÀ PW-500 and the mechanism of photoreduction process, DRS, EIS, i-t and PL tests were performed. [62][63][64] Compared with the DRS (Figure 5a) of ZnTiÀ PW 12 and ZnTi-LDH, it can be found that the absorption edge of ZnTiÀ PW 12 increases. After calcining ZnTiÀ PW 12 at 500 °C, the adsorption edge shifts to higher wavelength region even to the visiblelight region, indicating that calcination at 500 °C improves the absorption of visible light irradiation, which may be ascribed to PW 12 and the heterojunctions structure of ZnO and TiO 2 .…”
Section: Photoelectrochemical Propertiesmentioning
confidence: 95%
“…Water and air pollution are increasing concern all over the world as a risk of human health . Air pollution can cause asthma, skin irritation, nausea, cancer, brain damage, birth defects, respiratory and heart problems due to gaseous pollutants and particulate matter (PM) .…”
Section: Introductionmentioning
confidence: 99%
“…Water and air pollution are increasing concern all over the world as a risk of human health. [1][2][3] Air pollution can cause asthma, skin irritation, nausea, cancer, brain damage, birth defects, respiratory and heart problems due to gaseous pollutants and particulate matter (PM). [4][5][6][7][8] Based on inhalable particle size, PM is classified into coarse (2.5-10 μm), fine (0.1-2.5 μm) and ultrafine (< 0.1 μm).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, conventional methods are almost infeasible in industries because of excessive time and energy consumption. 21 There are some improvements on this field in recent years. For example, Chen et al synthesized a magnetic SPB (MSPB), which contained magnetic nanoparticles as the solid core for the magnetic separation of SPBs from solution.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods and strategies have been developed to separate nanoparticles from substrates according to their chemical or size differences, such as ultrafiltration and centrifugation. , Unfortunately, it is still a challenge to fully separate and recover them by conventional methods because of the strong interaction between nanoparticles and separation materials. Moreover, conventional methods are almost infeasible in industries because of excessive time and energy consumption . There are some improvements on this field in recent years.…”
Section: Introductionmentioning
confidence: 99%